Testing method of real stone paint roller marks

By measuring the color difference value ΔE between the adjacent interfaces of the real stone paint coating, it quickly determines whether there is a roll mark in the real stone paint, which solves the problem of lack of a rapid testing method in the existing technology, and accurately judges and improves the roll mark in the real stone paint, avoiding unnecessary losses after construction.

CN119845872APending Publication Date: 2025-04-18NIPPON PAINT GUANGZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411860767.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing technology lacks unified methods or standards to quickly test real stone paint roller marks, resulting in uneven color difference and roller marks after construction, affecting the appearance of the building and causing unnecessary losses.

Method used

By spraying real stone paint on the surface of the sheet without primer, one primer and two primer, the color difference value ΔE between adjacent interfaces is measured using a color difference meter to determine whether there is a roller mark. The color difference value ΔE≤1.0 is determined to be no roller marks, and ΔE>1.0 is determined to be a roller mark.

Benefits of technology

This test method can quickly and accurately determine whether there is a roller marking problem in real stone paint, and improve the roller marking by adjusting the formula of real stone paint to avoid unnecessary losses after construction and ensure the beauty of the building and wall protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845872A_ABST
    Figure CN119845872A_ABST
Patent Text Reader

Abstract

The invention discloses a real stone paint roller mark testing method, and relates to the technical field of quality detection. The testing method comprises the following steps: taking a plate, uniformly dividing the surface into three parts, respectively carrying out primer-free treatment, primary primer treatment and secondary primer treatment, then spraying real stone paint, and carrying out chromatic aberration measurement on the dried real stone paint by utilizing a colorimeter; in the three adjacent parts, it is judged that no roller mark exists when the color difference value delta E between two adjacent interfaces is smaller than or equal to 1.0, and it is judged that the roller mark exists when the color difference value delta E is larger than 1.0. According to the testing method, the evaluation grade of the roller mark is established, whether the roller mark phenomenon exists in the real stone paint or not can be rapidly judged, and therefore countermeasures are taken before construction, and losses are avoided. Therefore, the test method can be used for improving the roll mark problem of the real stone paint before construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quality inspection, and in particular to a method for testing roller marks of real stone paint. Background Art

[0002] As a new type of building decoration material, the current status and development trend of real stone paint show a positive trend. The market demand for real stone paint continues to grow, mainly due to the continuous development of the real estate market, the advancement of old city renovation, new rural construction and other projects, as well as consumers' increasing requirements for the quality of building decoration. Real stone paint is widely welcomed because of its realistic stone effect, which makes the decorative surface look more textured and three-dimensional. With the development of technology, the production technology of real stone paint has also been continuously improved, and the product performance has been improved, providing more choices for the market.

[0003] However, the real stone paint on the market still has various problems when applied, such as cracking, peeling, color difference, etc., especially the problem of uneven color difference after construction, which leads to roller marks and other phenomena, directly affecting the appearance of the building, making the building lose its due beauty, thus causing unnecessary losses after construction, seriously restricting the development and application of real stone paint. However, there is currently a lack of unified methods or standards to quickly test the roller marks of real stone paint and make regulations and explanations. Therefore, how to quickly judge the roller marks of real stone paint and quickly take improvement measures to deal with it is very meaningful for the development and application of real stone paint. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a test method for roller marks of real stone paint, establish an evaluation grade of roller marks, and use the color difference value as a measurement standard to quickly determine whether the real stone paint has roller marks.

[0005] The second aspect of the present invention is to provide an application of a method for testing roller marks of real stone paint.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a method for testing a real stone paint roller mark, comprising the following steps:

[0008] Take the board, divide the surface into three parts, and perform no primer treatment, one primer treatment, and two primer treatments respectively, then spray the real stone paint, and use a colorimeter to measure the color difference of the real stone paint after drying;

[0009] In the three adjacent parts, if the color difference value ΔE≤1.0 between two adjacent interfaces is determined to be without roller marks, and if the color difference value ΔE>1.0 is determined to be with roller marks.

[0010] Among them, the two-coat primer treatment refers to applying the primer twice, that is, applying another primer on top of the first primer.

[0011] The testing method of the present invention establishes an evaluation grade for roller marks, and uses the color difference value as a standard to determine whether there is a roller mark problem by testing the color difference of the real stone paint on the adjacent interfaces of the same surface. The testing method is not only simple and efficient, but also can accurately determine the roller mark of the real stone paint, which is conducive to quickly judging and implementing improvement measures for the roller mark before construction, avoiding the occurrence of roller marks and the like after construction, which directly affects the appearance of the building and causes unnecessary losses after construction.

[0012] In some embodiments of the present invention, the board material comprises a fiber cement board or a Chevron board.

[0013] In some embodiments of the present invention, the plate is cured at a temperature of 23-27° C. and a humidity of 48-52% after the treatment.

[0014] In some embodiments of the present invention, the curing time of the plate after the treatment is 3 to 5 hours.

[0015] In some embodiments of the present invention, the spraying gas pressure of the spraying real stone paint is 0.5-1 MPa.

[0016] In some embodiments of the present invention, the consumption of the real stone paint sprayed is 2-3 kg / m 2 .

[0017] In some embodiments of the present invention, the consumption of the real stone paint on the three parts of the board is the same, that is, the real stone paint is evenly sprayed on the surface of the board.

[0018] In some embodiments of the present invention, the plate is cured at a temperature of 23-27° C. and a humidity of 48-52% after the treatment.

[0019] In some embodiments of the present invention, the curing time of the plate after spraying the real stone paint is 23 to 25 hours.

[0020] In some embodiments of the present invention, the length of the plate is 400-450 mm, and the width is 130-170 mm.

[0021] The second aspect of the present invention provides an application of the testing method described in the first aspect of the present invention in improving roller marks of real stone paint.

[0022] The testing method of the present invention can be used to determine whether the real stone paint has the problem of roller marks, so as to improve the formula of the real stone paint before construction and avoid the loss caused by roller marks after construction. Therefore, it can be used to improve the roller marks of real stone paint before construction.

[0023] In some embodiments of the present invention, the method for improving the roller mark of real stone paint comprises the following steps:

[0024] The real stone paint is tested according to the method described in the first aspect of the present invention to determine the roller mark; the components of the real stone paint are adjusted to improve the roller mark.

[0025] After judging whether there is a roller mark problem by the testing method of the present invention, the roller mark of the real stone paint can be effectively improved before construction by improving the formula of the real stone paint, and the phenomenon of poor aesthetic effect caused by the color difference of the real stone paint can be eliminated. At the same time, the improved real stone paint can also protect the wall more effectively, and can be applied to various buildings with high requirements on the wall surface, such as theme parks, museums, gymnasiums, government office buildings and other public buildings, and has broad market prospects.

[0026] In some embodiments of the present invention, the mass content of white sand in the adjusted components of the real stone paint is 5-10%.

[0027] By limiting the amount of white sand added, improving the hiding power of real stone paint and adjusting the thixotropy, the color difference between the interfaces of real stone paint is reduced, and the roller mark phenomenon of real stone paint is effectively solved.

[0028] In some embodiments of the present invention, the real stone paint also includes water, emulsion, cellulose, film-forming aid, colored sand, titanium dioxide slurry and other additives.

[0029] In some embodiments of the present invention, the mass content of cellulose in the adjusted components of the real stone paint is 0.15-3%.

[0030] In some embodiments of the present invention, the improved real stone paint comprises the following components by weight:

[0031] 5-15 parts of water, 0.2-2 parts of cellulose, 10-20 parts of emulsion, 0.2-1.0 parts of film-forming aid, 5-10 parts of white sand, 50-80 parts of colored sand, 0.1-0.5 parts of titanium dioxide slurry, and 1-5 parts of other additives.

[0032] In some embodiments of the present invention, the cellulose is hydroxyethyl cellulose and / or hydroxypropyl cellulose.

[0033] In some embodiments of the present invention, the film-forming aid includes dodecyl alcohol ester.

[0034] In some embodiments of the present invention, the other auxiliary agents include at least one of a defoaming agent, an antifreeze agent, a pH regulator, and a preservative.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The test method provided by the present invention establishes an evaluation grade for roller marks. By using the color difference value as a measurement standard, it can quickly determine whether the real stone paint has the problem of roller marks and the extent of the roller marks. In addition, the test method is simple and easy to operate, can be widely used in practical applications, can quickly discover the roller mark phenomenon, and avoid unnecessary huge losses after construction.

[0037] (2) The testing method of the present invention can quickly determine the roller mark phenomenon of real stone paint, and thus can be used to improve the roller mark of real stone paint. First, determine whether there is a roller mark problem through testing, and then adjust the formula of the real stone paint accordingly to improve the roller mark. Through the real stone paint improvement method of the present invention, the performance of the real stone paint is guaranteed without the occurrence of roller marks, achieving the effect of both three-dimensional beauty and easy construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Photo of a fiber cement board without roller marks after spraying real stone paint.

[0039] Figure 2 Photo of roller marks after spraying real stone paint on fiber cement board. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0041] The real stone paint used in the tests of Examples 1 to 4 includes the following components by mass: 12 parts of water, 0.3 parts of cellulose, 10 parts of emulsion, 0.6 parts of film-forming aid, 11 parts of white sand, 64 parts of colored sand, 0.1 parts of titanium dioxide slurry, and 2 parts of other additives;

[0042] Among them, water is deionized water, cellulose is hydroxyethyl cellulose, emulsion is pure acrylic emulsion, film-forming aid is dodecanol ester, white sand is RS white sand, colored sand is natural colored sand, titanium dioxide slurry is 50% R-996 titanium dioxide slurry, and other additives include 0.7 parts of defoaming agent, 0.8 parts of antifreeze agent, 0.2 parts of pH adjuster, and 0.3 parts of preservative by weight. The defoaming agent is mineral oil defoaming agent, the antifreeze agent is ethylene glycol, the pH adjuster is a multifunctional amine additive, and the preservative is a 1,2-benzisothiazol-3-one preservative.

[0043] The real stone paint used in Example 5 is commercially available real stone paint purchased from Shenyang Shunfeng Paint Co., Ltd.

[0044] The primers used in the embodiments are all of the same type, which are conventional commercially available special primers for real stone paints, and their main components are water, cellulose, emulsion, film-forming aid, pH regulator, defoamer, antifreeze agent, bactericide and thickener.

[0045] The comparison of the photos with and without roller marks in the examples can be referred to Figure 1 (corresponding to Example 2) and Figure 2 (Corresponding to Example 1).

[0046] The following describes in detail different embodiments.

[0047] Example 1

[0048] A method for testing a real stone paint roller mark comprises the following steps:

[0049] S1. Take the fiber cement board and divide it into three parts. The three parts are treated with three different methods: no primer, one primer and two primers; one primer has a wet film thickness of 100 μm, and two primers are applied twice with a wet film thickness of 200 μm;

[0050] S2. Spray the treated fiber cement board with real stone paint. After the paint film is dry, quickly judge whether there is roller mark according to the color difference of the real stone paint under three different treatment methods;

[0051] Wherein, step S1 comprises:

[0052] S11. Take a fiber cement board with a length of 420 mm and a width of 150 mm;

[0053] S12. Use a ruler to divide the fiber cement board into three parts: a, b, and c, with a length of 140 mm and a width of 150 mm;

[0054] S13. a is treated without primer, b is treated with one primer, and c is treated with two primers;

[0055] S14. Curing for 4 hours under standard conditions of temperature 25±2℃ and humidity 50%;

[0056] Step S2 includes:

[0057] S21. Use a real stone paint spray gun (caliber about 5mm) to spray the treated fiber cement board at 2.5kg / m 2 The real stone paint consumption is used for real spraying construction, and the spraying air pressure is 0.8~0.9MPa;

[0058] S22. Place the fiber cement board after spraying the real stone paint under standard conditions (temperature 25±2℃, humidity 50%) for 24h;

[0059] S23. The color difference of the dried real stone paint was measured using a colorimeter;

[0060] The color difference between two adjacent interfaces of the three parts of the fiber cement board surface measured by the colorimeter was ΔE=2.63, and roller marks appeared on the surface.

[0061] Example 2

[0062] A method for testing a real stone paint roller mark comprises the following steps:

[0063] S1. Take the fiber cement board and divide it into three parts. The three parts are treated with three different methods: no primer, one primer and two primers; one primer has a wet film thickness of 100 μm, and two primers are applied twice with a wet film thickness of 200 μm;

[0064] S2. Spraying the treated fiber cement board with real stone paint, and after the paint film dries, quickly determine whether there is a roller mark according to the color difference of the real stone paint under three different conditions;

[0065] S3. In the case of roller marks, improve the formula of real stone paint, eliminate the influence of color difference of real stone paint, and improve its roller marks;

[0066] Wherein, step S1 comprises:

[0067] S11. Take a fiber cement board with a length of 420 mm and a width of 150 mm;

[0068] S12. Use a ruler to divide the fiber cement board into three parts: a, b, and c, with a length of 140 mm and a width of 150 mm;

[0069] S13. a is treated without primer, b is treated with one primer, and c is treated with two primers;

[0070] S14. Curing for 4 hours under standard conditions of temperature 25±2℃ and humidity 50%;

[0071] Step S2 includes:

[0072] S21. Use a real stone paint spray gun (caliber about 5mm) to spray the treated fiber cement board at 2.5kg / m 2 The real stone paint consumption is used for real spraying construction, and the spraying air pressure is 0.8~0.9MPa;

[0073] S22. Place the fiber cement board after spraying the real stone paint under standard conditions of temperature 25±2℃ and humidity 50% for 24h;

[0074] S23. The color difference of the dried natural stone paint was measured using a colorimeter. The result showed that the color difference between two adjacent interfaces of the three parts of the fiber cement board surface was ΔE=2.63. At this time, the natural stone paint had roller marks.

[0075] In step S3, the formula of the real stone paint is adjusted, and the improved real stone paint includes the following components in parts by mass:

[0076] 9.7 parts of water, 0.4 parts of cellulose, 12 parts of emulsion, 0.8 parts of film-forming aid, 10 parts of white sand, 65 parts of colored sand, 0.1 parts of titanium dioxide slurry, and 2 parts of other additives.

[0077] The improved real stone paint was again subjected to a roller mark test according to the test method of this embodiment, and a color difference value ΔE=0.83 was obtained. At this time, no roller mark appeared on the surface.

[0078] Example 3

[0079] A method for testing a real stone paint roller mark comprises the following steps:

[0080] S1. Take the fiber cement board and divide it into three parts. The three parts are treated with three different methods: no primer, one primer and two primers; one primer has a wet film thickness of 100 μm, and two primers are applied twice with a wet film thickness of 200 μm;

[0081] S2. Spraying the treated fiber cement board with real stone paint, and after the paint film dries, quickly determine whether there is a roller mark according to the color difference of the real stone paint under three different conditions;

[0082] S3. In the case of roller marks, optimize the formula of real stone paint to eliminate the influence of color difference of real stone paint and improve its roller marks;

[0083] Wherein, step S1 comprises:

[0084] S11. Take a fiber cement board with a length of 420 mm and a width of 150 mm;

[0085] S12. Use a ruler to divide the fiber cement board into three parts: a, b, and c, with a length of 140 mm and a width of 150 mm;

[0086] S13. a is treated without primer, b is treated with one primer, and c is treated with two primers;

[0087] S14. Curing for 4 hours under standard conditions (temperature 25±2℃, humidity 50%);

[0088] Step S2 includes:

[0089] S21. Use a real stone paint spray gun (caliber about 5mm) to spray the treated fiber cement board at 2.5kg / m 2 The real stone paint consumption is used for real spraying construction, and the spraying air pressure is 0.8~0.9MPa;

[0090] S22. Place the fiber cement board after spraying the real stone paint under standard conditions of temperature 25±2℃ and humidity 50% for 24h;

[0091] S23. The color difference of the dried real stone paint was measured using a colorimeter. The color difference between the two adjacent interfaces was ΔE = 2.63. At this time, the surface of the real stone paint had roller marks;

[0092] In step S3, the formula of the real stone paint is adjusted, and the improved real stone paint includes the following components in parts by mass:

[0093] 11.7 parts of water, 0.5 parts of cellulose, 10 parts of emulsion, 0.6 parts of film-forming aid, 9 parts of white sand, 66 parts of colored sand, 0.2 parts of titanium dioxide slurry, and 2 parts of other additives.

[0094] After improvement, the color difference of real stone paint is ΔE=0.61, and no roller marks appear on its surface.

[0095] Example 4

[0096] A method for testing a real stone paint roller mark comprises the following steps:

[0097] S1. Take the Chevron board and divide it into three parts. The three parts are treated with three different methods: no primer, one primer and two primers; one primer has a wet film thickness of 100 μm, and two primers are applied twice with a wet film thickness of 200 μm;

[0098] S2. Spray the treated fiber cement board with real stone paint. After the paint film dries, quickly determine whether there are roller marks based on the color difference of the real stone paint under three different conditions.

[0099] Wherein, step S1 comprises:

[0100] S11. Take a Chevron plate with a length of 420 mm and a width of 150 mm;

[0101] S12. Use a ruler to divide the Chevron board into three equal parts: a, b, and c, with a length of 140 mm and a width of 150 mm;

[0102] S13. a is treated without primer, b is treated with one primer, and c is treated with two primers;

[0103] S14. Curing for 4 hours under standard conditions of temperature 25±2℃ and humidity 50%;

[0104] Step S2 includes:

[0105] S21. Use a real stone paint spray gun (caliber about 5mm) to spray the treated Chevron board at 2.5kg / m 2 The real stone paint consumption is used for real spraying construction, and the spraying air pressure is 0.8~0.9MPa;

[0106] S22. Place the Chevron board after spraying the real stone paint under standard conditions of temperature 25±2℃ and humidity 50% for 24h;

[0107] S23. The color difference of the dried real stone paint was measured using a colorimeter, and the color difference between two adjacent interfaces was measured to be ΔE=2.65. At this time, the real stone paint had roller marks.

[0108] Example 5

[0109] A method for testing a real stone paint roller mark comprises the following steps:

[0110] S1. Take the fiber cement board and divide it into three parts. The three parts are treated with three different methods: no primer, one primer and two primers; one primer has a wet film thickness of 100 μm, and two primers are applied twice with a wet film thickness of 200 μm;

[0111] S2. Spraying the treated fiber cement board with real stone paint, and after the paint film dries, quickly determine whether there is a roller mark according to the color difference of the real stone paint under three different conditions;

[0112] Wherein, step S1 comprises:

[0113] S11. Take a fiber cement board with a length of 420 mm and a width of 150 mm;

[0114] S12. Use a ruler to divide the fiber cement board into three parts: a, b, and c, with a length of 140 mm and a width of 150 mm;

[0115] S13. a is treated without primer, b is treated with one primer, and c is treated with two primers;

[0116] S14. Curing for 4 hours under standard conditions of temperature 25±2℃ and humidity 50%;

[0117] Step S2 includes:

[0118] S21. Use a real stone paint spray gun (caliber about 5mm) to spray the treated fiber cement board at 2.5kg / m 2 The real stone paint consumption is used for real spraying construction, and the spraying air pressure is 0.8~0.9MPa;

[0119] S22. Place the fiber cement board after spraying the real stone paint under standard conditions of temperature 25±2℃ and humidity 50% for 24h;

[0120] S23. The color difference of the dried real stone paint was measured using a colorimeter, and the color difference between adjacent interfaces was measured to be ΔE=3.92, indicating roller marks.

[0121] In combination with the above-mentioned Examples 1 to 5, it can be seen that the test method of the present invention can accurately and effectively determine whether there is a roller mark problem in the real stone paint. When the real stone paint has a roller mark, the color difference value ΔE>1.0, and when there is no roller mark, the color difference value ΔE≤1.0. The test method can effectively determine the roller mark of the real stone paint before construction, so as to improve the formula of the real stone paint in a targeted manner and avoid the loss caused by the roller mark problem after construction.

[0122] The present invention further applies the test method to improve the roller marks of real stone paint. By adjusting the formula of real stone paint, especially the mass content of white sand, the hiding power of real stone paint is increased, and the thixotropy of real stone paint is adjusted, the phenomenon of roller marks of real stone paint is eliminated, and the unsightly roller marks caused by the color difference of the surface of real stone paint are solved, providing a more comfortable visual experience. In addition, it also provides longer-term protection for the wall, has strong practicality, and has broad market application prospects.

[0123] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for testing the roller marks of real stone paint, characterized in that: The steps include: Take the board, divide the surface into three parts, and perform no primer treatment, one primer treatment, and two primer treatment respectively, then spray the real stone paint, and use the colorimeter to measure the color difference of the real stone paint after drying; In the three adjacent parts, if the color difference value ΔE≤1.0 between two adjacent interfaces is determined to be without roller marks, and if the color difference value ΔE>1.0 is determined to be with roller marks.

2. The testing method according to claim 1, characterized in that: The board material comprises a fiber cement board or a Chevron board.

3. The testing method according to claim 1, characterized in that: After the treatment, the plate is cured under the conditions of a temperature of 23-27° C. and a humidity of 48-52%.

4. The testing method according to claim 1, characterized in that: The spraying pressure of the real stone paint is 0.5-1MPa; And / or, the consumption of the real stone paint sprayed is 2-3 kg / m 2 .

5. The testing method according to claim 1, characterized in that: After the treatment, the plate is cured under the conditions of a temperature of 23-27° C. and a humidity of 48-52%.

6. The testing method according to claim 3 or 5, characterized in that: The curing time of the plate after the treatment is 3 to 5 hours; And / or, the curing time of the plate after spraying the real stone paint is 23 to 25 hours.

7. Use of the testing method according to any one of claims 1 to 6 in improving roller marks of real stone paint.

8. The use according to claim 7, characterized in that: The method for improving the real stone paint roller mark comprises the following steps: The real stone paint is tested according to the method described in any one of claims 1 to 6 to determine the roller mark; the components of the real stone paint are adjusted to improve the roller mark.

9. The use according to claim 8, characterized in that: In the adjusted components of the real stone paint, the mass content of white sand is 5-10%.

10. The use according to claim 9, characterized in that: The real stone paint also includes water, emulsion, cellulose, film-forming aid, colored sand, titanium dioxide slurry and other additives.